ROTOR DYNAMICS OF MO DERN TURBOCHARGERS - Tomáš Fryščok (Perner’s Contacts, 2012)
Target of this article is to determine eigenvalues of the rotating parts of TC by series of measurement and subsequently to compare them with the predicted data from calculating software. The data were measured at the compressor side on a special compressor nut which is used especially for shaft motion measurement. The TC was installed on the internal combustion engine. The measurement was done within several loads and increasing oil inlet pressures and temperatures.